New approaches in bovine spermatozoa evaluation and their relationship with male fertility - Assumpção, Mayra Elena Ortiz D'Ávila; Hamilton, Thais Rose dos Santos [UNESP] (Elsevier, 2025)
Male fertility potential depends on physical, endocrine, and genetic factors responsible for producing functional male gametes. Although the main function of the male gamete, the spermatozoon, is to deliver its genetic material to the oocyte, this premise has been modified over the past few years. It is believed that the spermatozoon provides essential factors for fertilization and pre-implantation embryo development. A viable/healthy spermatozoon has functional subcellular compartments (nucleus, acrosome, midpiece, and flagellum) due to the actions of proteins, transcripts, and epigenetic marks in the organelles present in them that have important roles in reproductive biology. Male fertility potential reflects viable spermatozoa with proper function. Therefore, new approaches to functional sperm analysis are essential. Additionally, intrinsic factors and sperm molecules constitute potential biomarkers of viable spermatozoa and male fertility. Among these factors are proteins, the genome, and coding and non-coding RNAs, such as microRNAs, that act during fertilization and early embryo development. Research has been seeking increasingly efficient tools to predict fertility and functional studies of these molecules through gene and protein expression. Thus, analytical tools are essential to identify and classify viable and functional spermatozoa, to evaluate assisted reproductive male potential.
Keywords: MicroRNAs; Protamine; Sperm attributes; Sperm Chromatin; Sperm viability